PENGARUH GAYA SELF CHECK DAN CONVERGENT TERHADAP KEMAMPUAN DRIBBLING PEMAIN SEPAKBOLA SSB SANGGAR KEGIATAN BELAJAR MUARA BUNGO - ikhsanmaulana putra (Jurnal Muara Pendidikan, 2018)
Based on the observation of the writer it can be indicated that low level of ability of football player base of SSB SKB MuaraBungo. There are some factors caused this, such as exercise methods, physical conditions, nutritional status and infrastructure facilities. This study aims to explain the influence of the self-inspection style and the convergent style of the dribbling ability of football. The population in this study is SSB players SKB MuaraBungo (U.13-U.15) which amounted to 75 people. The sampling technique was purposive sampling with 30 samples.Moreover, the data of dribbling soccer capability is taken by the coach and the research team. The test instrument is dribbling test. Data analysis technique using t test. The result of data analysis shows that: 1) there is impact of self-check force toward dribbling ability of player SSB SKB MuaraBungo with t test 7,132>ttable 2,145; 2) the impact of convergent style on dribbling ability of SSB players SKB MuaraBungo with t test 7,613>ttable 2,145,3 ) self-check style is more effective than convergent style to increase dribbling ability of SSB SKB player with tcount of 7,132>ttable 2,145 for self check style and ttest result 7,613>ttable 2,145 for convergent style, which means there is difference between the two styles.